Rancang Bangun Sistem PPIC (Production Planning and Inventory Control) CV. DEA AYU LESTARI - Komara, Mutiara Andayani; Yusuf, Relavi Ahmad; Salim, Asep Yusapra; Wahyuni, Rani Sri; Heryana, Ghany (Journal of Applied Mechanical Technology, 2023)
CV. Dea Ayu Lestari is a company that operates as a collector and seller of solid waste from factory production. In this company, a small part of the PPIC system is being tested to gain an overview of how the system would work in a large manufacturing company. The data processing process is already computerized but still limited. Some of the newly available data processing processes include processing stock information, which includes incoming and outgoing goods data, as well as stock reports.The system development method used is the Waterfall method, and the development tool utilizes Unified Modeling Language (UML) modeling. This system is created using PHP version 5.4.7 and the database utilizes MySQL version 5.5.27. The result is an information management system for processing company data that allows administrators to quickly, accurately, and computerize the data recapitulation process. It covers stock data, incoming and outgoing goods, employee attendance, payroll, financial reports, and sales reports. Likewise, the company director can easily access information in the form of reports such as stock reports, incoming and outgoing goods reports, employee attendance reports, payroll reports, financial reports, and sales reports for the company they manage.